Systematic documentation and analysis of human genetic variation in hemoglobinopathies using the microattribution approach - Giardine, B; Borg, J; Higgs, D; Peterson, K; Philipsen, S; Maglott, D; Singleton, B; Anstee, D; Basak, A; Clark, B; Costa, F; Faustino, P; et al. (2011)
We developed a series of interrelated locus-specific databases to store all published and unpublished genetic variation related to hemoglobinopathies and thalassemia and implemented microattribution to encourage submission of unpublished observations of genetic variation to these public repositories. A total of 1,941 unique genetic variants in 37 genes, encoding globins and other erythroid proteins, are currently documented in these databases, with reciprocal attribution of microcitations to data contributors. Our project provides the first example of implementing microattribution to incentivise submission of all known genetic variation in a defined system. It has demonstrably increased the reporting of human variants, leading to a comprehensive online resource for systematically describing human genetic variation in the globin genes and other genes contributing to hemoglobinopathies and thalassemias. The principles established here will serve as a model for other systems and for the analysis of other common and/or complex human genetic diseases. © 2011 Nature America, Inc. All rights reserved.